Apalancamiento fiscal y costo de capital de terceros para empresas brasileñas - Cardoso Duarte, Joseane Martins (2022)
This study empirically investigates whether Brazilian companies that are more tax-leveraged have a lower capital cost from third parties than those that are less tax-leveraged. The survey data comprises financial information from 315 companies listed on the stock exchange - B3 and was structured containing information on the total liabilities due (PET), tax liabilities (PT), and the third parties’ capital cost (ki) of the sampled companies for the years between 2013 to 2017. The research is descriptive, with a quantitative approach, using methods of descriptive statistics and Pearson’s Correlation Coefficient for data analysis. The results indicate that the tax leverage provides a lower capital cost for third parties compared to the companies’ other onerous liabilities in the sample analyzed, proving, in this paper, that the financial strategy of not collecting taxes and using these resources to finance the activities of the companies can generate savings in the capital cost of third parties. The research contributes academically to provide an opportunity for discussion on the topic, contributes to society by exposing the public policy implications of granting tax installments, and contributes to companies by indicating the possibility of reducing the cost of third-party capital via tax leverage.